2015
DOI: 10.1016/j.freeradbiomed.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Age-related loss of hepatic Nrf2 protein homeostasis: Potential role for heightened expression of miR-146a

Abstract: Summary Nrf2 regulates the expression of numerous anti-oxidant, anti-inflammatory, and metabolic genes. We observed that, paradoxically, Nrf2 protein levels decline in the livers of aged rats despite the inflammatory environment evident in that organ. To examine the cause(s) of this loss, we investigated the age-related changes in Nrf2 protein homeostasis and activation in cultured hepatocytes from young (4-6 months) and old (24-28 months) Fischer 344 rats. While no age-dependent change in Nrf2 mRNA levels was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Previous studies have demonstrated that miR-146a-5p contributes to the senescence of hepatocytes 54 , macrophages 55 , and endothelial cells 56 . Similarly, miR-146a-5p can be as a marker of senescence-related pro-inflammatory status in the vasculature 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that miR-146a-5p contributes to the senescence of hepatocytes 54 , macrophages 55 , and endothelial cells 56 . Similarly, miR-146a-5p can be as a marker of senescence-related pro-inflammatory status in the vasculature 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, miRNA-146a was reported to inhibit Nrf2 protein synthesis, but maintaining Nrf2 mRNA levels, in aging rats28. Luteolin was also reported to inhibit procarcinogenic miRNAs53.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor (erythroid-derived 2)-like 2 (Nrf2) was described as being important for the antioxidant response25, antiinflammatory response26, and cytoprotection of hepatocytes27. A recent study showed that miRNA-146a regulated Nrf2 translation through binding to Nrf2 mRNA in aging28. Sirtuin type 1 (Sirt1), a NAD + -dependent histone deacetylase strongly expressed in the liver, is intimately related to cell proliferation, differentiation, apoptosis, and metabolism29.…”
mentioning
confidence: 99%
“…Nrf2 knockout old mice display reduced gene and protein expression of antioxidant enzymes and increased apoptosis in skeletal muscle, suggesting a contribution of defective Nrf2 to sarcopenia (Miller et al, 2012). The mechanisms leading to the reduction Nrf2 signaling despite an inflammatory and oxidant environment associated with aging are not clear but it has been proposed that the agingrelated up-regulation of the microRNA 146a, which binds to Nrf2 RNA, contributes to the reduced Nrf2 protein content and the attenuated expression of Nrf2-dependent genes after stimulation in hepatocytes from aged rats (Smith et al, 2015). Thus, although the available evidence is scarce, the key role of Nrf2 in controlling cellular response to stress makes the enhancement Nrf2 signaling an interesting target for evaluation with the aim to prevent/reverse the frailty phenotype.…”
Section: Article In Pressmentioning
confidence: 99%